Teachers' readiness to use technology in the classroom: an empirical study - Samy, Naresh Kumar; Che Rose, Raduan; Alby, Jeffrey Lawrence D'Silva (EuroJournals Publishing, 2008)
The growing body of literature associated with educational computer use has examined numerous variables and interrelationships in order to gain a better understanding of computer beliefs and use of computers within education. Teachers' computer acceptance is an important factor to the successful use of computers in education. Thus there is a need to examine the factors affecting teachers' computer use and its implications to teachers' professional development strategies. This article reports a research on the relationship between actual usage of computer (AUC) and technology acceptance constructs among secondary school Mathematics, Science and English language (MSE) teachers in Malaysia. Overall, the study found that the AUC among MSE secondary school teachers were at the moderate level. Meanwhile, the constructs of attitude, perceived usefulness, perceived ease of use, job relevance, and computer compatibility showed significant positive relationship with AUC. Practical recommendations for school administrators and teachers been discussed.